Dataset for: Baseline Survey of the Project "Group-Based ICT Extension Systems: Evidence from Rural Areas of Peru" in the Provinces of Sanchez Carrion and Pataz, La Libertad Region - Suarez, V.; Pradel, W.; Fonseca, C.; Otiniano, R. (2024)
Baseline Survey: In this baseline data, we collect information about household’s socio-economic characteristics, plots, past production, participation in previous extension projects, etc. This provides information to further analyze heterogeneous effects of the treatment amongst specific subgroups (i.e., by age, gender, etc.). We also administer questionnaires to gauge farmers’ baseline agricultural knowledge and will use this data to group communities into different tournament brackets (see above). The baseline survey was conducted from October 14 to 25, 2024, covering the districts of Huamachuco, Curgos, Chugay, and Cochorco in the province of Sánchez Carrión, as well as the districts of Tayabamba, Pataz, and Pias in the province of Pataz. A total of 1,389 potato producers were surveyed.